One-stage vs. two-stage brachio-basilic arteriovenous fistula for dialysis access: a systematic review and a meta-analysis. - Khalid Bashar; Donagh A Healy; Sawsan Elsheikh; Leonard D Browne; Michael T Walsh; Mary Clarke-Moloney; Paul E Burke; Eamon G Kavanagh; Stewart R Walsh (PLoS ONE, 2015)
Introduction A brachiobasilic arteriovenous fistula (BB-AVF) can provide access for haemodialysis in patients who are not eligible for a more superficial fistula. However, it is unclear whether one- or two-stage BB-AVF is the best option for patients. Aim To systematically assess the difference between both procedures in terms of access maturation, patency and postoperative complications. Methods Online search for randomised controlled trials (RCTs) and observational studies that compared the one-stage versus the two-stage technique for creating a BB-AVF. Results Eight studies were included (849 patients with 859 fistulas), 366 created using a one-stage technique, while 493 in a two-stage approach. There was no statistically significant difference between the two groups in the rate of successful maturation (Pooled risk ratio = 0.95 [0.82, 1.11], P = 0.53). Similarly, the incidence of postoperative haematoma (Pooled risk ratio = 0.73 [0.34, 1.58], P = 0.43), wound infection (Pooled risk ratio = 0.77 [0.35, 1.68], P = 0.51) and steal syndrome (Pooled risk ratio = 0.65 [0.27, 1.53], P = 0.32) were statistically comparable. Conclusion Although more studies seem to favour the two-stage BVT approach, evidence in the literature is not sufficient to draw a final conclusion as the difference between the one-stage and the two-stage approaches for creation of a BB-AVF is not statistically significant in terms of the overall maturation rate and postoperative complications. Patency rates (primary, assisted primary and secondary) were comparable in the majority of studies. Large randomised properly conducted trials with superior methodology and adequate sub-group analysis are needed before making a final recommendation.